Who are the 10%? - Non eligibility of cystic fibrosis (CF) patients for highly effective modulator therapies. (August 2022) - Desai, Maya; Hine, Chris; Whitehouse, Joanna L.; Brownlee, Keith; Charman, Susan C.; Nagakumar, Prasad
Abstract: Background: The availability of mutation-specific cystic fibrosis modulator therapies has the potential to improve the lives of children and adults with cystic fibrosis. The frequency of mutations causing defects in the cystic fibrosis transmembrane conductance regulator (CFTR) function varies between sub-groups in multi-ethnic populations. The profile of patients eligible for CFTR modulator ivacaftor/tezacaftor/elexacaftor (Kaftrio™) therapy based on ethnicity has not been reported in the United Kingdom CF population. Methods: We conducted a descriptive cross-sectional analysis of patients in the UK CF Registry who had annual review data submissions in 2019. Data analysed included demographic characteristics, spirometry, chronic Pseudomonas status, nutrition, and CF related diabetes status. The genotype data was stratified by whether there was at least one copy of F508del or no copy of F508del as current eligibility for ivacaftor/tezacaftor/elexacaftor, or projected future eligibility, is defined as having at least one copy of F508del mutation. Results: Data from 9887 patients were reviewed, 46.7% female, mean age 22.5 years. 8.6% (n = 852) patients had no copy of F508del making them ineligible for ivacaftor/tezacaftor/elexacaftor. Overall, 93.4% of patients were of white ethnicity, with a similar proportion of those with at least one F508del being white (95.6%). This was reduced to 70.0% of those with no F508del. The proportion of people of Asian ethnicity was much higher in the no F508del group (19.2% vs 1.2%). Compared with one F508del patients, the no F508del group were older (25.2 years vs 22.2 years, p < 0.001), had higher prevalence of pancreatic sufficiency (39.0% vs 14.9% p < 0.001), lower prevalence of chronic Pseudomonas infection (21.1% vs. 26.6%, p < 0.001), and higher best FEV1 from the previous year (proportion with greater than 70% FEV1 predicted, 66.1% vs 63.0%, p = 0.005). Conclusion: Patients from black, Asian and minority ethnic backgrounds are significantly less likely to be eligible for ivacaftor/tezacaftor/elexacaftor based on the current prescribing policy in the UK. At present this is the most highly effective CF modulator therapy available to treat people with CF. The CF community should urgently address the unmet need for effective targeted therapies for patients without F508del. Highlights: Patient data from the UK Cystic Fibrosis Registry was studied. This analysis describes those ivacaftor/tezacaftor/elexacaftor (Kaftrio™) eligible. 8.6% of the UK Cystic Fibrosis population will not be eligible. Patients from minority ethnic backgrounds are less likely eligible.